Artificial Intelligence and the Law : cybercrime and criminal liability (New York: Routledge, 2022)
This volume presents new research in Artificial Intelligence and Law with special reference to criminal justice. It will be a valuable resource for academics and researchers working in the areas of AI, Technology and Criminal Justice.
Keywords: Artificial Intelligence -- Law and Legislation; Criminal Provision -- Computer Crimes